cAMP/PKA signaling and RIM1α mediate presynaptic LTP in the lateral amygdala - Fourcaudot, Elodie (National Academy of Sciences, 2008)
NMDA receptor-dependent long-term potentiation (LTP) of glutamatergic synaptic transmission in sensory pathways from auditory thalamus or cortex to the lateral amygdala (LA) underlies the acquisition of auditory fear conditioning. Whereas the mechanisms of postsynaptic LTP at thalamo–LA synapses are well understood, much less is known about the sequence of events mediating presynaptic NMDA receptor-dependent LTP at cortico–LA synapses. Here, we show that presynaptic cortico–LA LTP can be entirely accounted for by a persistent increase in the vesicular release probability. At the molecular level, we found that signaling via the cAMP/PKA pathway is necessary and sufficient for LTP induction. Moreover, by using mice lacking the active-zone protein and PKA target RIM1α (RIM1α(−/−)), we demonstrate that RIM1α is required for both chemically and synaptically induced presynaptic LTP. Further analysis of cortico–LA synaptic transmission in RIM1α(−/−) mice revealed a deficit in Ca(2+)-release coupling leading to a lower baseline release probability. Our results reveal the molecular mechanisms underlying the induction of presynaptic LTP at cortico–LA synapses and indicate that RIM1α-dependent LTP may involve changes in Ca(2+)-release coupling.